"Ma ten kościół różne odpusty, osobliwie na dni Nayśw. Maryi Panny na niedziele brackie y inne święta". Uwagi o nadaniach odpustowych kościoła mariackiego w Krakowie - Szymborski, Wiktor (Analecta Cracoviensia, 2011)
The purpose of the article was to show the characteristics of religiousness of society in the medieval Cracow on the basis of an analysis of indulgences issued by Mariacki church. For this purpose, the list of all indulgences granted from XIV up to XVI century was presented as well as the changes occurring in their text in the time. In the next part of the article all occasions and conditions that had to be fullfilled in order to be granted an indulgences were summarized in tables. Mention is also made of indulgences bestowed on confraternities. Attention was given to the propaganda actions of the medieval citizens in order to receive another indulgences granted to the Mariacki Church and the amount of the days and years of indulgence period as well. Indulgences were granted for participation in a procession, going on a pilgrimage and giving alms to the Mariacki church. The author noted that in three diplomas that granteed indulgences the expression ad instar - equivalent indulgences was used. It should be interpreted that indulgences connected with Corpus Christi feast and indulgences of Wenetian cathedral were granted. The Mariacki Church flourished also due to its possesion of a famous altars donated by wealthy Cracow family and large processions from Wawel Castle. Another key reason for the growth of the Mariacki Church was indulencese granted in the 14th and 15th centuries.